ENGLISH STUDENT BOOK EVALUATION IN SCHOOL BASED CURRICULUM (KTSP) CONTEXT : A Case Study of "English Student Book" Published by Directorate General Management of Primary and Secondary Education Nomor Panggil TBING MAR e-2012 - Matra, Sarlita Dewi (2012)
This thesis is the study of evaluation to an English Student Textbook used in all junior high schools in Pekalongan. This study is guided by three research questions: 1) What are the strengths and weakneses of the textbook presented in the book? 2) What are the teachers' perceptions toward the book in SMP N 2 Pekalongan? 3) What are the relevancies of the materials found in the book toward KTSP? This study employs both quantitative and qualitative analyses of data. The quantitative strategy analyses the frequency and percentage on respondents' answers toward the questionnaire. The questionnaire consisted of predetermined context for which the respondents were asked to report their perceptions toward the book in use. A questionnaire-based interview was employed to seek comments on the respondents' answers to the questionnaire. The combined investigative technique elicited ample data that enable the researcher to control the interplay of variables. In addition, a qualitative checklist analyses was used to evaluate the relevancies of the materials presented in the book toward School Based Curriculum. The study finds the strengths of the book in some aspects and weaknesses on the others. In short, the textbook fulfills criteria of a good textbook in term of practical consideration which concerns with accessibility and physical characteristics. In term of layout and design, the textbook seems to be organized effectively. In addition, the textbook seems to present appropriate materials considering learners interest and needs, the right level of language, authenticity of language and the coverage of materials recommended by the current curriculum. Moreover, the textbook seems to not contain gender bias and negative stereotypes. Aside from its strengths, the textbook seems to have weaknesses in terms of the unavaibility of the authors' credentials and teachers' guides. Regarding language skills and activities, the textbook seems to fail to present language skills proportionally. Furthermore the unbalance portion of activities has become the textbook drawback. Furthermore, it seems that teachers know some criteria of good textbook. They perceived positively toward the book in general. This book covers around 83,58% of students' needs, since this book provides almost off materials required in KTSP, only 16, 42% materials which are not relevant to the KTSP. These findings can be used as background information to set further study for the betterment of the material development. Key Words: Evaluation, English Student Book, School Based Curriculum KTSP